Speech improvement activities for the educable mentally retarded children - Medalle, Hedy S. 1941-; Saquido, Rizalina D.; Valdes, Matilde M. (Quezon City College of Education, University of the Philippines Diliman, 1968)
The aim of the study was to present suitable classroom activities which the teacher can utilize for the speech improvement of the educable mentally retarded. The study is a compilation of the readings from the different books and journals in the education library and the main library of the University of the Philippines and from the Bureau of Public Schools Library. The researcher found out that a speech improvement program has a place in the school as seen from the results of the studies made. Although effects gained were not abruptly great, the improvement in articulation and in the use of a meaningful speech was evident.
"April, 1968."
Vita.
Thesis (Master of Arts in Teaching - Special Education)--University of the Philippines, Diliman.
Keywords: Children with mental disabilities -- Education (Prumary) -- Philippines; Oral communication -- Study and teaching (Primary) -- Activity programs -- Philippines